Proceedings of the First International Conference on Technology and Educational Science 2019
DOI: 10.4108/eai.21-11-2018.2282297
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Family Ownership on the Relationship Between Aggressive Financial And Tax Reporting: Evidence From 10 Asian Countries

Abstract: This research aims to investigate the nature of the relationship between aggressive financial and tax reporting, and the influence of family ownership upon that relationship. Using crosscountry data of public companies listed on the stock exchanges of 10 countries in Asia, this study finds that aggressive financial reporting is associated positively with aggressive tax reporting and is reciprocal in nature, indicating that managers may no longer face a trade-off between the two. It is evident that managers hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…They concluded that financial distress had a positive relationship with tax avoidance and that the relationship between financial distress and tax avoidance had increased due to the global financial crisis. Warsini et al (2018) found that financial distress had a positive effect on tax aggressiveness. Based on the explanation above, the researchers predicted a positive influence between companies with financial distress and tax aggressiveness.…”
Section: Financial Distress and Tax Aggressivenessmentioning
confidence: 99%
“…They concluded that financial distress had a positive relationship with tax avoidance and that the relationship between financial distress and tax avoidance had increased due to the global financial crisis. Warsini et al (2018) found that financial distress had a positive effect on tax aggressiveness. Based on the explanation above, the researchers predicted a positive influence between companies with financial distress and tax aggressiveness.…”
Section: Financial Distress and Tax Aggressivenessmentioning
confidence: 99%